Pengenalan Permainan Tradisonal Engklek di Kalangan Generasi Z Melalui Sosial Media TikTok - Mursin Mursin; Hardin Hardin; Destin Destin; Hasmita Hasmita; Ainun Syahyatunnisa (Jurnal Bersama Pengabdian Kepada Masyarakat (SAMAMAS), 2026)
The traditional game of Engklek is a cultural heritage rich in educational, social, and cultural values ​​that urgently needs to be preserved amidst the rapid disruption of digital technology. The increasing intensity of gadget use has caused this folk game to be increasingly alienated from the daily lives of the younger generation. Responding to this phenomenon, this community service activity was initiated with the main objective of reintroducing the existence of the Engklek game to Generation Z by optimizing the use of social media as a means of education while promoting the preservation of local culture. The traditional game of Engklek is one of the cultural heritages that has educational, social, and cultural values ​​that need to be preserved. However, the development of digital technology and the increasing use of social media among Generation Z have caused traditional games to be increasingly less known and rarely played. This community service activity aims to reintroduce the traditional game of Engklek to Generation Z through the use of social media as a means of education and cultural preservation. The activity was carried out in Lorong Pelangi with 11 participants from Generation Z. The methods used included awareness, training, and mentoring through the delivery of materials regarding the history, rules of the game, benefits, and values ​​of local wisdom contained in the Engklek game. The results of the activity showed an increase in participants' knowledge, understanding, and interest in the traditional game of Engklek. The use of social media has proven effective in disseminating cultural information to the younger generation and supporting efforts to preserve traditional games as part of local cultural identity in the digital era.